Recent Publications (Quarterly Journal of Economics, 1939)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 53, Issue 3, May 1939, Pages 487–490, https://doi.org/10.1093/qje/53.3.487 Published: 01 May 1939